Vesicle-associated Membrane Protein 4 is Implicated in Trans-Golgi Network Vesicle Trafficking - Steegmaier, Martin (The American Society for Cell Biology, 1999)
The trans-Golgi network (TGN) plays a pivotal role in directing proteins in the secretory pathway to the appropriate cellular destination. VAMP4, a recently discovered member of the vesicle-associated membrane protein (VAMP) family of trafficking proteins, has been suggested to play a role in mediating TGN trafficking. To better understand the function of VAMP4, we examined its precise subcellular distribution. Indirect immunofluorescence and electron microscopy revealed that the majority of VAMP4 localized to tubular and vesicular membranes of the TGN, which were in part coated with clathrin. In these compartments, VAMP4 was found to colocalize with the putative TGN-trafficking protein syntaxin 6. Additional labeling was also present on clathrin-coated and noncoated vesicles, on endosomes and the medial and trans side of the Golgi complex, as well as on immature secretory granules in PC12 cells. Immunoprecipitation of VAMP4 from rat brain detergent extracts revealed that VAMP4 exists in a complex containing syntaxin 6. Converging lines of evidence implicate a role for VAMP4 in TGN-to-endosome transport.